[Students walk by finished College Union] - P. K. Phillips::::::photographer::: (1972)
Students travel on their way to class as they walk on the walkway surrounding the finished College Union. They appear as they are about to turn into the opening that connects the College Union to the rest of campus. A banner on the Union mezzanine reads: 'Homecoming '72 Oct. 20-21, 'A Sign of the Times''. Another banner advertises an invitation to join a student committee.